The biological role of N-acyl-homoserine lactone-based quorum sensing (QS) in EPS production and microbial community assembly during anaerobic granulation process. Issue 1 (December 2018) - Ma, Haijun; Ma, Sijia; Hu, Haidong; Ding, Lili; Ren, Hongqiang
Abstract Although N-acyl-L-homoserine lactone (AHL) based quorum sensing (QS) phenomenon has been observed in mature anaerobic granules, the biological role of AHL-based QS system in anaerobic granulation process remains unexplored. For the first time, a long-term anaerobic bioreactor was operated for 168 days to investigate the biological role of AHL in the granulation process which was divided into three phases (phase I: floccular, phase II: granulation, phase III: maturation). Two different AHLs including C8-HSL and C10-HSL were characterized at nanogram levels. The AHL level was elevated over 20-fold and strongly positively correlated with extracellular polymeric substances (EPS) production and sludge particle size during phase I-II. Exogenous addition of AHL to the floccular sludge also resulted in significantly increased EPS production. Metadata analysis suggested that the granulation process was accompanied by an increase in the abundance of QS-relevant microorganisms. The strong relationships (R > 0.9233, p < 0.01) among AHL concentrations, EPS (except loosely bound EPS), granulation and community variation indicated that AHL-mediated QS played an important role in coordinating community level behaviors associated with granulation, potentially through the regulation of EPS production and composition. This study gives a deep insight into the underlying QS-relevant mechanism of anaerobic granulation process.